Respiratory health challenges among construction workers in Chennai, India – A mixed-methods study - Vanitha Durai; Hemakairavi R; Ezhilarasan S; Samya V; Inba Raja A (Asian Journal of Medical Sciences, 2026)
Background: Construction workers in urban India, particularly in rapidly developing cities like Chennai, are exposed to high levels of occupational dust, increasing the risk of respiratory diseases such as chronic obstructive pulmonary disease, asthma, and allergic rhinitis. Aims and Objectives: This study aimed to assess the prevalence of respiratory health challenges, associated risk factors, and workers’ lived experiences. Materials and Methods: A sequential explanatory mixed-methods study was conducted among 200 construction workers selected through multistage sampling from construction sites across 10 administrative zones of Chennai between January and April 2026. Quantitative data were collected using the Indian Study on Epidemiology of Asthma, Respiratory Symptoms and Chronic Bronchitis questionnaire and objective peak expiratory flow rate (PEFR) measurements. This was followed by four rounds of focus group discussions involving 40 workers selected purposively from the quantitative cohort. Quantitative data were analyzed using descriptive statistics, Chi-square tests, and odds ratios (ORs), whereas qualitative data were analyzed thematically. Results: Prevalence of at least any one respiratory morbidity was 37.5% (95% confidence interval [CI]: 30.8–44.2), whereas low PEFR was observed at 50.5% (95% CI: 43.6–57.4). Significant associations included age >35 years (OR: 3.664, P=0.000), total exposure period >100 (OR: 4.620, P